Italian Contemporary Screen Performers
XIX, 303 p. 2 illus.
Keywords: “Looking beyond the finished product of the actor’s performance, this essential collection illuminates the work of screen acting. Presenting a diverse range of case studies, chapters provide valuable insights into the formation of career pathways, the roles played by assorted intermediaries in managing actor, and the uses of various media outlets to generate promotional exposure.” — Paul McDonald, King’s College, UK “This book offers fascinating explorations of actors’ trajectories, including the ways they manage their age and their aging and how they broker off-screen activities, making this an especially useful and rich resource in Italian screen studies.” — Ellen Nerenberg, Wesleyan University, USA “This volume magnificently expands the geographical and media reach of star studies, demonstrating the ways in which contemporary, non-Hollywood stardom is and is not appropriately understood through the established paradigms. Furthermore, star studies have long been bedevilled by an emphasis on the star image at the expense of the work that goes into producing such images. Here the volume is triumphant, brilliantly covering all bases.” — Richard Dyer, King’s College, UK This open access book brings together performance studies, celebrity studies, and media production studies, and it offers a comprehensive understanding of the multi-layered condition of film and television performers within the contemporary Italian screen media landscape. By focusing on a selection of stars who reached success from 2000 onwards, the collection highlights how the renewal of the Italian media industry in the late 1990s impacted different aspects of Italian screen performers’ professional lives, from training to promotion and validation strategies. Luca Barra is Professor of Television and Media Studies at the Department of the Arts, Università di Bologna, Bologna, Italy Cristina Formenti is Lecturer in Film Studies at the Department of Arts, Culture and Media, University of Groningen, Groningen, The Netherlands Mariapaola Pierini is Professor of Film Studies at the Department of Humanities, Università degli Studi di Torino, Torino, Italy Francesco Pitassio is Professor of Film Studies at the Department of Humanities and Cultural Heritage, Università degli Studi di Udine, Udine, Italy.